Cushing’s disease disrupts functional brain network topology - Xu, Can-xin; Jiang, Hong; Zheng, Ruizhe; Sun, Yu-Hao; Sun, Qing-Fang; Bian, Liu-Guan (Dryad, 2019)
ABSTRACT Objective: To investigate the whole functional brain networks of
active Cushing disease (CD) patients about topological parameters (small
world and rich club et al.) and compared with healthy control (NC).
Methods: Nineteen active CD patients and twenty-two healthy control
subjects, matched in age, gender, and education, underwent resting-state
fMRI. Graph theoretical analysis were used to calculate the functional
brain networks organization of all participants and compare between active
CD and NC. Results: Active CD patients revealed higher global efficiency,
less path length and cluster efficiency compared with healthy control.
Additionally, small word organization was present in active CD patients
but higher than healthy control. Moreover, rich club connections, feeder
connections and local connection were significantly decreased in active CD
patients. Conclusions: The functional network properties were disrupted in
active CD patients compared with healthy control. Analyzing the changes of
abnormal network metrics is helpful to understand the pathophysiological
mechanism.